Distinct roles of Bazooka and Stardust in the specification of Drosophila photoreceptor membrane architecture - Hong, Yang (National Academy of Sciences, 2003)
Photoreceptors form during Drosophila pupal development and acquire elaborate membrane structures, including the rhabdomeres and stalk membranes. Here, we show that the development of these cellular structures involves two distinct processes: the establishment of apical–basal polarity that requires Bazooka (Baz), and the regionalization of apical membrane into stalk membranes and rhabdomeres that requires Stardust (Sdt). In the absence of Baz, the apical–basal polarity is compromised in early pupal photoreceptors, and no identifiable apical membrane domain is formed. Sdt, in contrast, plays a more limited role in apical–basal polarity but is essential for the proper localization of transmembrane protein Crumbs (Crb), known to be required in the biogenesis of stalk membrane. Loss of Sdt causes strong defects in stalk membrane and rhabdomere resembling crb mutant phenotype. Thus, proteins required for establishing the early embryonic epithelial polarity are used later for the morphogenesis of photoreceptors, with Baz and Sdt functioning in different aspects of the formation of the apical–basal cellular architecture.